Dendritic cell subsets in T cell programming: location dictates function - Eisenbarth, S. C. (Nat Rev Immunol, 2019)
Dendritic cells (DCs) can be viewed as translators between innate and adaptive immunity. They integrate signals derived from tissue infection or damage and present processed antigen from these sites to naive T cells in secondary lymphoid organs while also providing multiple soluble and surface-bound signals that help to guide T cell differentiation. DC-mediated tailoring of the appropriate T cell programme ensures a proper cascade of immune responses that adequately targets the insult. Recent advances in our understanding of the different types of DC subsets along with the cellular organization and orchestration of DC and lymphocyte positioning in secondary lymphoid organs over time has led to a clearer understanding of how the nature of the T cell response is shaped. This Review discusses how geographical organization and ordered sequences of cellular interactions in lymph nodes and the spleen regulate immunity.